'Everybody's Scottish at the end of the day': Nationalism and Social Justice Amongst Young Yes Voters. Issue 4 (November 2015) - Breeze, Maddie; Gorringe, Hugo; Jamieson, Lynn; Rosie, Michael
Abstract : In the wake of the diverse mobilization for Yes in the 2014 Independence Referendum and unprecedented SNP gains in the 2015 General Election, a number of commentators deployed a rhetoric of 'dangerous nationalism' by way of explanation and criticism. Such an interpretation is refuted by survey evidence and complicated by sociologies of nationalism and national identity. This short article joins these debates, and presents analysis of ten explorative interviews conducted with young Yes voters between the Referendum and the General Election. There is no simple narrative of 'nationalism' in these young people's accounts. Some explicitly distanced themselves from nationalist sentiment, emphasising a commitment to social justice as their key motivation for Yes. Others shared this primary concern but expressed it as overlapping with a national(ist) identity in complex ways. While disavowals of 'romantic' or 'narrow' nationalism occur on both sides of the independence debate, this study points to how more banal, and nuanced discourses of national(ist) identity underpin respondents' explanations for voting Yes.